Modelling of a capillary discharge soft x-ray laser / Teh Chew Peng - Teh, Chew Peng (2013)

(untitled)
This work presents a numerical study of a Neon-like Argon capillary discharge xray laser. We outline the theoretical framework and present the results of the numerical investigations of a one-dimensional single-fluid magneto-hydrodynamics (MHD) model,with separate electron and ion temperatures, of a capillary-discharge collisional soft xray laser. The MHD equations are solved by the Lagrangian cylindrical geometry approach. The effects of the gas filling pressure on the plasma densities and temperatures during the implosion-pinch phase have been investigated. In addition, gas filling pressure effects on the laser intensity for soft x-ray lasing conditions at a wavelength of 46.9 nm of argon filled gas inside the capillary have been analyzed. The results are compared with experimental measurements at the operating pressure ranges (0.1 – 0.4 mbar). Besides this, other input parameters such as capillary radius, peak current and current rise-time have also been considered in this study to optimize lasing conditions. The MHD model has also been studied to investigate the possibility of a nitrogen x-ray laser operating at the wavelength of 13.4 nm.